Defibrotide improved the outcome of monocrotaline induced rat hepatic sinusoidal obstruction syndrome - Zhenli Liu; Shan Liang; Xinhuan Wei; Xiaofei Du; Jing Zhang (BMC Gastroenterology, 2022)
Abstract Background and aim Pyrrolizidine alkaloids (PA) induced hepatic sinusoidal obstruction syndrome (HSOS) occurred worldwide and the mortality rate remained high because there were no specific therapies. Defibrotide was effective for HSOS following hematopoietic stem cell transplantation. But the pathogenesis of the two types of HSOS were not equivalent. The purpose of this study was to see if defibrotide was also effective in PA induced rat HSOS. Methods First we improved rat HSOS model by using higher dose (230 mg/kg) of monocrotaline (a kind of PA) as the dose of median lethal dose. So drug effectiveness could be assessed by survival time. Next, male SD rats were divided into 5 groups. They were control group, model group, low dose low molecular weight heparin (LMWH) treatment group, high dose LMWH treatment group and defibrotide treatment group. Rats’ survival time, liver function, white blood cell count and cytokines were compared among the groups. The DeLeve score was used to assess the severity of liver pathology. Results The model group exhibited typical liver pathology of HSOS, such as hepatic sinus dilation, congestion, endothelial injury of central lobular vein, coagulative necrosis of hepatocytes and fibrin deposition in the subendothelial. The pathologic characteristics indicated that the model was built up successfully. The survival rate was significantly higher in defibrotide group (81.8%) than model group (43.7%), while the survival rates were similar in the two LMWH groups (62.5% and 75%) and model group. The survival time only be prolonged by defibrotide (P=0.028) but not LMWH (P>0.05). DeLeve score was improved most in the defibrotide group than the two LMWH groups (both P<0.01). Changes in DeLeve score, liver function, plasma level of tumor necrosis factor α and plasminogen activator inhibitor-1 exhibited the same trends. Conclusion Defibrotide could improve the outcome of monocrotaline-induced rat HSOS indicating that defibrotide might be a better choice than LMWH in clinical practice.